1987
DOI: 10.1002/ceat.270100123
|View full text |Cite
|
Sign up to set email alerts
|

Fluid dynamics and mass transfer in a bubble column with suspended particles

Abstract: Slurry bubble columns are widely used in biotechnology . Therefore, the effects of solid particles on fluidization characteristics, gas hold-up and volumetric liquid-side mass transfer coefficient were measured in a slurry bubble column (i.d. 0.14 m). The density and diameter of the suspended particles were similar to those applied in biotechnology with immobilized bacteria. Based on models of turbulence and of liquid circulation induced by rising gas bubbles, equations for critical gas velocity, gas hold-up a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 19 publications
5
31
2
Order By: Relevance
“…Muller and Davidson (1992) have shown that small-class bubbles contribute 20-50 % of the gas-liquid mass transfer in a column with highly viscous liquid. Addition of solid particles to liquid in a bubble column reduces the gas holdup and correlations of gas holdup valid for transition and heterogeneous flow regimes were proposed by Koide et al (1984), Sauer and Hempel (1987) and Salvacion et al (1995). Wilkinson et al (1992) have summarized some of the most important gas holdup correlations and have discussed the role of gas density.…”
Section: Estimation Of Gas Holdupmentioning
confidence: 99%
See 1 more Smart Citation
“…Muller and Davidson (1992) have shown that small-class bubbles contribute 20-50 % of the gas-liquid mass transfer in a column with highly viscous liquid. Addition of solid particles to liquid in a bubble column reduces the gas holdup and correlations of gas holdup valid for transition and heterogeneous flow regimes were proposed by Koide et al (1984), Sauer and Hempel (1987) and Salvacion et al (1995). Wilkinson et al (1992) have summarized some of the most important gas holdup correlations and have discussed the role of gas density.…”
Section: Estimation Of Gas Holdupmentioning
confidence: 99%
“…For these cases, Koide et al (1984) and Yasunishi et al (1986) proposed correlations for k L a prediction. Sauer and Hempel (1987) proposed k L a correlations for bubble columns with suspended particles. Sada et al (1986) and proposed correlations for k L a prediction in bubble columns with solid particles of diameter less than 10 µm.…”
Section: Estimation Of Volumetric Liquid-phase Mass Transfer Coefficientmentioning
confidence: 99%
“…The results can provide references for bubble column design. The bubble column features simple structure, easy operation, cost efficiency and excellent scrubbing factor as compared with other scrubbers (Chen et al, 2008;Lin et al, 2003;Sauer and Hempel, 1987;Aroonwilas et al, 1999), without mechanical heat production. Thus, recovery of CO2 using bubble columns can reduce costs and save energy.…”
Section: Introductionmentioning
confidence: 99%
“…The liquid may flow through the column either with or against the gas flow. Investigations of bubblecolumns from the viewpoints of both environmental problems and industrial use can be found in the literature (Juvekar & Sharma, 1973;Sada et al, 1985;Sauer & Hempel, 1987;Okawa et al, 1999;Chen et al, 2002;Hamid & Jones, 2002;Lapin et al, 2002). Bubble column reactors are widely used in the chemical, petrochemical, biochemical, and metallurgical industries (Degaleesan & Dudukovic, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some investigators (Sauer & Hempel, 1987;Hamid & Jones, 2002) have studied the dynamics, mass transfer, and control of the crystal size and shape of products for industrial purposes. However, these data cannot be utilized effectively.…”
Section: Introductionmentioning
confidence: 99%